Jawapan

2016-01-27T23:47:39+08:00
4x - 3x-1 = 4 - 5x+1
x - 1 = -5x + 5
x + 5x = 5 + 1
6x = 6
x = 6/6
x = 1

beza sepunya ,d,
T2-T1
d=4x-3x-1
d=4(1)-3(1)-1
d=4-3-1
d=0

T8=a+(n-1)d
= 2+(8-1)(1)
= 2+7
=9


* a=3x-1
=3(1)-1
=2

but the answer in the text book is x= 1/3 , d= 4/3 , t8= 9/1/3. thanks for the help btw :)
ohh...sori2 sy lupa letak kurungan..
2016-01-28T01:09:11+08:00
4x - (3x -1) = 4 - (5x +1)
4x -3x +1 = 4 -5x -1
x +1 = 3 -5x
6x = 2
x = 2/6
x = 1/3

d = 4 - (5x +1)
d = 4 -5x -1
d = 3 -5x
d = 3 -5(1/3)
d = 3 -5/3
d = 9/3 -5/3
d = 4/3

a = 3x -1
a = 3(1/3) -1
a = 0

T8
= a + 7d
= 0 + 7(4/3)
= 28/3
= 9 1/3